Tanggung Jawab Pidana Terhadap Masyarakat Yang Mengajak Orang Lain Untuk Golput Dalam Pemilu - Grasiara Naya S; Hana Faridah, Hana Faridah; Masrifah, Masrifah; Din Eri Pratama, Din Eri Pratama (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
The practice of abstaining is still a massive phenomenon that occurs during the election season in Indonesia. In fact, data from the Central Statistics Agency (BPS) shows that the number of people who abstained in 2019 was 34.75 million or around 18.02% of the total registered voters. Meanwhile, in 2014, the number of abstainers was 58.61 million people or 30.22%. This means that citizen participation in the democratic system in Indonesia is still not good. Intentional abstention from voting is now classified as a criminal act (delict) which is expressly contained in the General Election Law Number 7 of 2017 (UU ELECTION). In its implementation, Indonesia adheres to the principle of legal fiction, where the public is assumed to know the applicable law (presumptio iures de iure). Therefore, with the provisions of regulations containing strict criminal sanctions leading up to the 2024 elections, it is hoped that citizens will become more aware and obedient to applicable laws. Criminal liability would be a solution to prevent the practice of abstaining from voting ahead of the next election.